Light ID and HMD-AR Based Interactive Exhibition Design for Jeonju Hanok Village Immersive 3D View - Byung-Jun Min(민병준); Vinayagam Mariappan(비나야감 마리아판); Jae-Sang Cha(차재상); Dae-Young Kim(김대영); Ju-Phil Cho(조주필) (한국정보전자통신기술학회 논문지, 2018)
The digital convergence looking for new ways to engage visitors by superimposing virtual content on projection over the real world captured media contents. This paper propose the Light ID based interactive 3D immersive exhibition things view using HMD AR technology. This approach does not required to add any additional infrastructure to be built-in to enable service and uses the installed Lighting or displays devices in the exhibit area. In this approach, the Light ID can be used as a Location Identifier and communication medium to access the content unlike the QR Tag which supports provide the download information through web interface. This utilize the advantages of camera based optical wireless communication (OWC) to receive the media content on smart device to deliver immersive 3D content visualization using AR. The proposed exhibition method is emulated on GALAXY S8 smart phone and the visual performance is evaluated for Jeonju Hanok Village. The experimental results shows that the proposed method can give immersive 3D view for exhibit things in real-time. KCI Citation Count: 0